Sistem Antrian Cucian Mobil Berbasis Website Menggunakan Konsep CRM dan Penerapan UML: Application of UML with the Concept of CRM (Customer Relationship Management) in the Website-Based Car Wash Queue Scheduling System (Komputika : Jurnal Sistem Komputer, 2022)
– The progress of information and communication technology is very fast, making all aspects of being have to follow it. One of them is the business world, by utilizing information and communication technology, will increase efficiency in all fields. This discussion is about how to design a car wash queue scheduling application system with the concept of CRM (Customer Relationship Management). CRM is a business strategy that combines processes, people, and technology to make a business process more effective and efficient by utilizing designed technology. In designing the infrastructure for this Web-based application system, it is necessary to have a design model, namely UML (Unified Modeling Language). UML is a common model and is most widely used in helping the system design process so that it is necessary to apply UML modeling correctly both in theory and case study design, both the structure of the actors involved, the activities of each actor, the processes and mechanisms of the Website-based Car Wash Queue Scheduling system. this. The programming language used is the PHP (Hypertext Preprocessor) programming language and MySql (My Structured Query Language) database. The application of UML modeling can provide design ease in helping the coding process become a Website-Based Car Wash Queue Scheduling System Application. With this application, it can provide convenience for both the owner and customer from the transaction taking place online and well computerized.